Collisional Quantum Dynamics for MgH− (1Σ+) With He as a Buffer Gas: Ionic State-Changing Reactions in Cold Traps - González-Sánchez, Lola; Gómez-Carrasco, Susana; Santadaría, Alberto M.; Wester, Roland; Gianturco, Francesco A. (Frontiers in Chemistry, 2019)
We present in this paper a detailed theoretical and computational analysis of the quantum 4 inelastic dynamics involving the lower rotational levels of the MgH-(X1Sigma+) molecular anion in 5 collision with He atoms which provides the buffer gas in a cold trap. The interaction potential 6 between the molecular partner and the He (1S) gaseous atoms is obtained from accurate 7 quantum chemical calculations at the post-Hartree-Fock level as described in this paper. The 8 spatial features and the interpretation strength of the present potential energy surface (PES) 9 are analysed in detail and in comparison with similar, earlier results involving the MgH+ (1Sigma) 10 cation interacting with He atoms. The quantum, multichannel dynamics is then carried out using 11 the newly obtained PES and the final inelastic rats constants, over the range of temperatures 12 which are expected to be present in a cold ion trap experiment, are obtained to generate the 13 multichannel kinetics of population changes observed for the molecular ion during the collisional 14 cooling process. The rotational populations finally achieved at specific temperatures are linked 15 to state-selective laser photo-detachment experiments to be carried out in our laboratory. All 16 intermediate steps of the quantum modelling are also compared with the behaviour of the 17 corresponding MgH+ cation in the trap and the marked differences which exist between the 18 collisional dynamics of the two systems are discussed and explained. The feasibility of the present 19 anion to be involved in state-selective photo-detachment experiments is fully analysed and 20 suggestions are made for the best performing conditions to be expected during trap experiments.